Molecular footprinting of skeletal tissues in the catshark Scyliorhinus canicula and the clawed frog Xenopus tropicalis identifies conserved and derived features of vertebrate calcification - Enault, Sebastien; Muñoz, David N.; Silva, Willian T.; Borday-Birraux, Véronique; BONADE, Morgane; OULION, Silvan; Ventéo, Stéphanie; Marcellini, Sylvain; Debiais-Thibaud, Melanie (Frontiers in Genetics, 2015)
Understanding the evolutionary emergence and subsequent diversification of the vertebrate skeleton requires a comprehensive view of the diverse skeletal cell types found in distinct developmental contexts, tissues and species. To date, our knowledge of the molecular nature of the shark calcified extracellular matrix, and its relationships with osteichthyan skeletal tissues, remain scarce. Here, based on specific combinations of expression patterns of the Col1a1, Col1a2 and Col2a1 fibrillar collagen genes, we compare the molecular footprint of endoskeletal elements from the chondrichthyan Scyliorhinus canicula and the tetrapod Xenopus tropicalis. We find that, depending on the anatomical location, Scyliorhinus skeletal calcification is associated to cell types expressing different subsets of fibrillar collagen genes, such as high levels of Col1a1 and Col1a2 in the neural arches, high levels of Col2a1 in the tesserae, or associated to a drastic Col2a1 downregulation in the centrum. We detect low Col2a1 levels in Xenopus osteoblasts, thereby revealing that the osteoblastic expression of this gene was significantly reduced in the tetrapod lineage. Finally, we uncover a striking parallel, from a molecular and histological perspective, between the vertebral cartilage calcification of both species and discuss the evolutionary origin of endochondral ossification.